The impact of business strategies on choosing a supply chain strategy - أيسل حمدي عثمان; فلاح سليم فالح المياحي (Iraqi Journal for Administrative Sciences, 2025)
The times at which the customer accept what is offered to him is no longer existed, he is now chooses what he needs and what is suitable for him and he wants even the matter exceeded this, to the extent that the customer specified the price suitable to him, and the global competition, requires re- consider the follow-up strategies, and managing the affairs and the projects in a different no- n classical way . This research has discussed the business strategies as independent variable and the strategy of supply chain as dependent variable, and included the two variables and sub- variables and these variables has been interacted to form the frame on which the research has concentrated, and which aims at limiting the effect of business strategies in choosing the strategy of supply chain, and for constructing and developing the industrial sector in Iraq, it has chosen two companies as community for the research ( the state company for leather industries and the state company for wool industries), and choosing intended sample represented by the two and the first levels managers means the company managers and the departments manager of(60 ) manager form the two companies, and divided in to ( 30) manger from each company. The questionnaire has been depended as basic instrument to collect data and the form of personal interview to know the two companies reality concerning the research. And according of the measurement of the research variables and detecting them and examining the liaison correlation and the effect amongst them, the research has reached to a number of conclusion most important of them was the existence of correlation liaison and effect of significant evidence among the business strategies and the strategy supply chain in the two addressed companies, and the most important recommendations, the managers suitability and inconsistence of the business strategies with the strategy of provision series, and all the strategies required coordination decision from the upper administration.